The validity of progesterone level on hCG injection day in the prediction of IVF/ICSI cycles’ outcome - Abolfotouh, Mostafa A; Al-Anazi, Hallah; Hassan, Samar (Clinical Journal of Obstetrics and Gynecology, 2019)
Background: Previous studies highlighted the negative effect of premature progesterone elevation (PE) during IVF cycles on the cycle outcomes. The aim of this study was to assess the validity of progesterone level on hCG day (P4) in the prediction of IVF/ICSI cycles’ outcome. Methods: In a retrospective cohort study, all fresh cycles of 256 patients who underwent IVF or ICSI cycles in 2017 at reproductive endocrinology & infertility unit/ Obg/Gyn department at King Abdulaziz Medical city, Riyadh, Saudi Arabia, were followed up. They were started on gonadotropin medications for ovarian hyperstimulation, followed by serial transvaginal U/S and serum estrogen levels each visit. Patients having 2 or more 18mm follicles were triggered by hCG 10,000 IU and ovum pickup was done 34-36 hrs after. Data were collected on patients’ characteristics [age, BMI infertility type], cycles’ characteristics [number of follicles and endometrium thickness on hCG day, P4 and estrogen levels], rates of pregnancy and pregnancy outcomes. Receiver operating characteristic curve was applied to determine the cut-off of P4 that corresponds with a negative pregnancy test. Logistic regression analysis was used and significance was considered at p - value of ≤0.05. Results: Pregnancy rate in the study sample was 36.7%. The mean P4 level in cycles with negative pregnancy tests was significantly higher than the mean in cycles with positive tests (p = 0.018). After adjusting for confounders, significant negative association between P4 and pregnancy rate was evident (p < 0.03). The optimum trade-off of P4 for prediction of a negative pregnancy test was 1.5nmol/L. This cut-off level had a 59% sensitivity, 51% specificity and 68% positive predictive value and 10% & 15% absolute and relative risk reductions respectively. Cycles with mean P4 of ≥1.5nmol/L were significantly associated with primary infertility (p = 0.011), lower mean BMI (p = 0.009) higher mean estrogen level (p < 0.001), lower live birth rate (p = 0.048), higher abortion rate (p = 0.039), and higher ovarian hyperstimulation rate (p = 0.027). Conclusion: Premature elevation of progesterone level on the hCG day in IVF/ICSI cycles may have adversely impacted the pregnancy rate and pregnancy outcome. The cutoff point of 1.5nmol/L for this P4 was not valid in predicting pregnancy outcomes.